Comparison of Modified Mallampati Classification and Acromio-Axillo-Suprasternal Notch Index in Predicting Difficult Laryngoscopy: A Prospective cohort study. - Noufal P.K, Mohamed; Vishal, Padma Amar; Kommula , Gopala Krishna (Student’s Journal of Health Research Africa, 2025)
Background: Difficult airway management remains a major concern in anesthesia, with unanticipated intubation failures increasing perioperative morbidity and mortality. Accurate preoperative identification of at-risk patients is essential for safe airway management and reducing complications like hypoxia and failed intubation. Among airway assessment tools, the Modified Mallampati Classification (MMP) and Acromio-Axillo-Suprasternal Notch Index (AASNI) are commonly used. This study compared the predictive accuracy of MMP and AASNI in forecasting difficult visualization of the larynx (DVL) during direct laryngoscopy. Methods: A prospective cohort study was conducted on 106 adult patients aged between 18 and 60 years, scheduled for elective surgeries requiring general anesthesia and endotracheal intubation. Each patient underwent preoperative airway assessments using MMP and AASNI. During laryngoscopy, the Cormack-Lehane (CL) grading was recorded. Diagnostic parameters—sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), odds ratio, and likelihood ratios—were calculated to evaluate the predictive performance of MMP and AASNI. Results: Of the 106 participants, 58 (54.7%) were male and 48 (45.3%) were female. The mean age was 38.11 ± 9.88 years, with the majority aged 40–50 years (38.7%). The average BMI was 24.75 ± 2.33 kg/m². AASNI showed higher sensitivity (83.3%) and NPV (93.9%) compared to MMP (41.67% and 83.7%, respectively), while MMP had greater specificity (87.8%). Both tools shared equal PPV (50%) and diagnostic accuracy (77.36%). AASNI demonstrated a higher odds ratio (15.5 vs. 5.14) and lower negative likelihood ratio (0.220 vs. 0.664), confirming superior predictive performance. Conclusion: AASNI is a more reliable and objective predictor of difficult laryngoscopy than MMP. It enhances preoperative airway assessment and supports better preparedness for airway management. Recommendations: Routine use of AASNI is recommended in pre-anesthetic evaluations. Future multicentric studies with larger, diverse populations are warranted to further validate its effectiveness and generalizability.